NOTARY POSITION JURIDICAL REVIEW OF AQAD MURABAHAH FINANCING IN A SYARI'AH BANK MADE IN THE FORM OF NOTARY ASSET REVIEWED FROM NOTARY OFFICE LAW - Mahdinur, Mahdinur; Yusuf Rangkuti, Ramlan; Mustamam, Mustamam (LPPM YPITI, 2021)
The demand for notary competence in mastering shari'ah laws relating to the development of sharia economics aims so that notaries can cover all activities and make sharia aqad in the form of notarial deeds that are truly in accordance with the principles of shari'a Ah. The problem in this study is how is the legal certainty of a notary deed in making aqad shari'ah in financing Murabahah at a Sharia Bank made in the form of a notarial deed in terms of the Notary Position Act? How is the notary's ability to formulate the substance of the agreement based on the aqad of sharia in the city of Banda Aceh? How are the notary's obstacles and constraints in making aqad shari'ah in the form of a notary deed?. This type of research is empirical juridical research, while the nature of the study is descriptive analysis. The research data consisted of bersumbed data from primary and secondary data. The data analysis used in this study is qualitative data analysis.Based on the results of the study, the legal certainty of a notary deed in making aqad shari'ah can be said to have no legal certainty. Where the notarial deed is made on the financing aqad at the shari'ah bank, by the notary usually included the lafaz